Thermodynamic and kinetic parameters and high rate discharge-ability of the AB5-type metal hydride anode. (22nd June 2016) - Kaabi, Abbes; Khaldi, Chokri; Lamloumi, Jilani
Abstract: In this paper, we have studied the thermodynamic and the kinetic parameters as well as the high rate discharge-ability, at different temperatures after activation, of the iron-free LaNi3.55 Mn0.4 Al0.3 Co0.75 and the iron-containing LaNi3.55 Mn0.4 Al0.3 Co0.2 Fe0.55 alloys used as negative electrode materials in nickel-metal hydride batteries. Besides, we have examined the electrochemical properties of the iron-free LaNi3.55 Mn0.4 Al0.3 Co0.75 and the iron-containing LaNi3.55 Mn0.4 Al0.3 Co0.2 Fe0.55 alloys at ambient and at two other different temperatures. Several techniques, such as the galvanostatic charging and discharging as well as the constant potential discharge, have been applied to determine the previously-mentioned characteristics. The iron-containing alloy has shown less reversibility reaction and slow activation compared with the iron-free alloy. The values of the enthalpy and the entropy changes as well as the activation energy are respectively −40 kJ mol −1, 97 J K −1  mol −1, 12.27 kJ mol −1 and −36 kJ mol −1, 87 J K −1 mol −1, 14.07 kJ mol −1 for the iron-free and iron-containing hydrides. These values are in agreement with the results provided in the literature. For the low rates (0–100 mA g −1 ), the temperature does not significantly affect the HRD. Beyond 100 mA g −1, the HRD decreases rapidly with temperature. However, for the iron-containing electrode, the HRD remains more interesting than that in the iron-free electrode. Highlights: The iron-containing and iron-free electrodes are activated at the ambient temperature. The HRD of the iron-containing and iron-free electrodes was evaluated at different temperatures. The thermodynamic and the kinetic parameters of the iron-containing and iron-free electrodes were determined. The found thermodynamic and kinetic parameters are compared to those determined through the solid–gas dry method.